2015
DOI: 10.7555/jbr.29.20140151
|View full text |Cite
|
Sign up to set email alerts
|

Myocardin in biology and disease

Abstract: Myocardin (MYOCD) is a potent transcriptional coactivator that functions primarily in cardiac muscle and smooth muscle through direct contacts with serum response factor (SRF) over cis elements known as CArG boxes found near a number of genes encoding for contractile, ion channel, cytoskeletal, and calcium handling proteins. Since its discovery more than 10 years ago, new insights have been obtained regarding the diverse isoforms of MYOCD expressed in cells as well as the regulation of MYOCD expression and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 181 publications
(208 reference statements)
1
90
0
Order By: Relevance
“…Postnatal cardio-restricted MYOCD knockdown induces dilated cardiomyopathy and fatal HF in mice [69], while forced expression of MYOCD in ventricular myocardium impairs LV systolic function and cardiac ECG activity in pigs [70]. In light of these results, it comes as no surprise that a strong association between the altered expression of MYOCD and cardiac pathological conditions has been established in different animal models as well as patients with end-stage HF (reviewed in [23,67,68]). …”
Section: Heart Fail Revmentioning
confidence: 84%
See 2 more Smart Citations
“…Postnatal cardio-restricted MYOCD knockdown induces dilated cardiomyopathy and fatal HF in mice [69], while forced expression of MYOCD in ventricular myocardium impairs LV systolic function and cardiac ECG activity in pigs [70]. In light of these results, it comes as no surprise that a strong association between the altered expression of MYOCD and cardiac pathological conditions has been established in different animal models as well as patients with end-stage HF (reviewed in [23,67,68]). …”
Section: Heart Fail Revmentioning
confidence: 84%
“…One of such cofactors is myocardin (MYOCD) that regulates the expression of multiple smooth muscle (SM) and cardiac contractile genes, including CNN1 (calponin 1, basic, smooth muscle), MYH11 (myosin, heavy chain 11, smooth muscle), ACTA2 (actin, alpha 2, smooth muscle, aorta), ACTG2 (actin, gamma 2, smooth muscle), TAGLN (transgelin), and MYH6 (myosin, heavy chain 6, cardiac muscle, alpha) (reviewed in [23,[65][66][67][68]). …”
Section: Heart Fail Revmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previously characterized myocardin-associated factors either stabilize or disrupt the SRF-myocardin complex. 8 It is likely that Aggf1 may function as a scaffold to bring SRF and myocardin together. Alternatively, the ability of myocardin to associate with SRF is known to be modulated by post-translational modifications.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the ability of myocardin to associate with SRF is known to be modulated by post-translational modifications. 8,17 It has recently been shown that Aggf1 is able to modulate the activities of several kinases including extracellular signal-regulated kinase 18 Figure 3. Angiogenic factor with G patch and FHA domains 1 (Aggf1) is essential for serum response factor (SRF)-dependent transactivation of smooth muscle cell-specific genes.…”
Section: Discussionmentioning
confidence: 99%